BECOMING THE BEST VERSION: THE INTERPLAY OF SELF-REFLECTION, PERSONAL GROWTH, AND PSYCHOLOGICAL WELL-BEING - Mrs. S. Anithalakshmi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This article presents a comprehensive review of the literature on the interrelationship between personal growth, self-reflection, and psychological well-being. We explore the theoretical foundations of these concepts, examine empirical research findings, and discuss their implications for individuals and society. The review highlights the role of self-reflection in fostering personal development and its impact on psychological well-being. We also identify future directions for research and practical applications for promoting mental health through self-awareness and personal growth strategies.